Investigating Epidemiologic and Molecular Links Between Patients With Community- and Hospital-Acquired Influenza A: 2017–2018 and 2019–2020, Michigan. (8th February 2023) - Wan, Tiffany; Lauring, Adam S; Valesano, Andrew L; Fitzsimmons, William J; Bendall, Emily E; Kaye, Keith S; Petrie, Joshua G
Abstract: Background: Hospital-acquired influenza virus infection (HAII) can cause severe morbidity and mortality. Identifying potential transmission routes can inform prevention strategies. Methods: We identified all hospitalized patients testing positive for influenza A virus at a large, tertiary care hospital during the 2017–2018 and 2019–2020 influenza seasons. Hospital admission dates, locations of inpatient service, and clinical influenza testing information were retrieved from the electronic medical record. Time-location groups of epidemiologically linked influenza patients were defined and contained ≥1 presumed HAII case (first positive ≥48 hours after admission). Genetic relatedness within time-location groups was assessed by whole genome sequencing. Results: During the 2017–2018 season, 230 patients tested positive for influenza A(H3N2) or unsubtyped influenza A including 26 HAIIs. There were 159 influenza A(H1N1)pdm09 or unsubtyped influenza A–positive patients identified during the 2019–2020 season including 33 HAIIs. Consensus sequences were obtained for 177 (77%) and 57 (36%) of influenza A cases in 2017–2018 and 2019–2020, respectively. Among all influenza A cases, there were 10 time-location groups identified in 2017–2018 and 13 in 2019–2020; 19 of 23 groups included ≤4 patients. In 2017–2018, 6 of 10 groups had ≥2 patients with sequence data, including ≥1 HAII case. Two of 13 groups met this criteria in 2019–2020. Two time-location groups from 2017–2018 each contained 3 genetically linked cases. Conclusions: Our results suggest that HAIIs arise from outbreak transmission from nosocomial sources as well as single infections from unique community introductions.